PENGARUH KECERDASAN EMOSI, KEPUASAN KERJA DAN PERSEPSI TERHADAP TIPE KEPEMIMPINAN PELAYANAN (SERVANT LEADERSHIP) TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT SENTRA USAHATAMA JAYA - , Hira Andira Putri Lewenussa ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Related to the phenomenon of increasing levels of employee resignations at PT. Sentra Usahatama Jaya in November 2012 to January 2013, this study aims to examine the influence of emotional intelligence, job satisfaction and perceptions of servant leadership towards organizational commitment on SUJ Employees. The study was conducted to 293 SUJ employees from operator to manager level with tenure of 1 (one) year or above, with total sample 58% of the total population. The study was conducted using quantitative methods, that is by collecting data from respondents who fit with the characteristics of the sample, through emotional intelligence questionnaire (adapted from SREIT, made by Schutte, et al, 1998), job satisfaction questionnaire (adapted from JSS, made by Spector, 1997), perception of servant leadership questionnaire (adapted from SLAI, made by Dennis and Bocarnea, 2005), and organizational commitment questionnaire (adapted from OCQ, made by Mowday, et al, 1979). Multiple linear regression yield that (1) emotional intelligence has a positive correlation on organizational commitment of employees of PT. Sentra Usahatama Jaya